A Redwall winter's tale - Jacques, Brian; Denise, Christopher (London : Red Fox, 2003)
Funloving Bungo the molebabe and his friend Tubspike the hedgehog maid welcome a traveling troupe that visits Redwall Abbey to celebrate the coming of Snowbadger, the Lord of Wintertide.
Keywords: Animals -- Fiction; Winter -- Fiction